The Coevolution of RuBisCO, Photorespiration, and Carbon Concentrating Mechanisms in Higher Plants - Cummins, Peter L. (Frontiers in Plant Science, 2021)
Ribulose-1,5-bisphosphate (RuBP) carboxylase/oxygenase (RuBisCO) is the carbon-fixing enzyme present in most photosynthetic organisms, converting CO2 into organic matter. Globally, photosynthetic efficiency in ter-restrial plants has become increasingly challenged in recent decades due to a rapid increase in atmospheric CO2 and associated changes toward warmer and dryer environments. Well adapted for these new climatic conditions, the C4 photosynthetic pathway utilizes carbon concentrating mechanisms (CCMs) to increase CO2 concentrations surrounding RuBisCO, suppressing photorespiration from the oxygenase catalyzed reaction with O2. The energy efficiency of C3 photosynthesis, from which the C4 pathway evolved, is thought to rely critically on an uninterrupted supply of chloroplast CO2. Part of the homeostatic mechanism that maintains this constancy of supply involves the CO2 produced as a byproduct of photorespiration in a negative feedback loop. Analyzing the database of RuBisCO kinetic parameters, we suggest that in genera (Flaveria and Panicum) for which both C3 and C4 examples are available, the C4 pathway evolved only from C3 ancestors possessing much lower than the average carboxylase specificity relative to that of the oxygenase reaction (SC/O = SC/SO) and hence the higher CO2 levels required for development of the photorespiratory CO2 pump (C2 photosyn-thesis) essential in the initial stages of C4 evolution, while in the later stage (final optimization phase in the Fla-veria model) increased CO2 turnover may have occurred, which would have been supported by the higher CO2 levels. Otherwise, C4 RuBisCO kinetic traits remain little changed from the ancestral C3 species. At the opposite end of the spectrum, C3 plants (from Limonium) with higher than average SC/O, which may be associated with the ability of increased CO2, relative to O2, affinity to offset reduced photorespiration and chloroplast CO2 lev-els, can tolerate high stress environments. It is suggested that, instead of inherently constrained by its kinetic mechanism, RuBisCO possesses the extensive kinetic plasticity necessary for adaptation to changes in pho-torespiration that occur in the homeostatic regulation of CO2 supply under a broad range of abiotic environ-mental conditions.